2021
DOI: 10.1002/ecy.3333
|View full text |Cite
|
Sign up to set email alerts
|

While shoot herbivores reduce, root herbivores increase nutrient enrichment’s impact on diversity in a grassland model

Abstract: Nutrient enrichment is widespread throughout grassland systems and expected to increase during the Anthropocene. Trophic interactions, like aboveground herbivory, have been shown to mitigate its effect on plant diversity. Belowground herbivory may also impact these habitats' response to nutrient enrichment, but its influence is much less understood, and likely to depend on factors such as the herbivores' preference for dominant species and the symmetry of belowground competition. If preferential toward the dom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 93 publications
(117 reference statements)
2
10
0
Order By: Relevance
“…For grasslands, our findings confirmed that the effects of changes in compositional and configurational heterogeneity of below‐ground resources at fine centimeter‐size scales, as suggested by Schenk (2006), are indeed important. This aligns with recent studies by Crawford et al (2019, 2021), indicating that plant–plant interactions at such scales can be crucial for local plant community dynamics. In addition, plant responses to the spatial distribution patterns of nutrients are species‐specific.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…For grasslands, our findings confirmed that the effects of changes in compositional and configurational heterogeneity of below‐ground resources at fine centimeter‐size scales, as suggested by Schenk (2006), are indeed important. This aligns with recent studies by Crawford et al (2019, 2021), indicating that plant–plant interactions at such scales can be crucial for local plant community dynamics. In addition, plant responses to the spatial distribution patterns of nutrients are species‐specific.…”
Section: Discussionsupporting
confidence: 92%
“…To investigate the dynamics of the small‐scale heterogeneity–diversity relationship in a grassland community, we used a refined version of the dynamic IBC‐Grass model (an individual‐based model of grassland community) by May et al (2009), which simulates the fate of individual plants over time depending on above‐ and below‐ground resource availability. With this model, different scenarios of plant–plant and plant–environmental interactions have been tested, for example, the effects of varying nutrient content and mowing (May et al, 2009), shoot and root herbivory (Crawford et al, 2021), and habitat isolation on plant communities (Weiss et al, 2014). Other examples include the effects of below‐ground herbivory on the community (Körner et al, 2014; Pfestorf et al, 2016; Crawford et al, 2021), influence of grazing cessation (Weiss & Jeltsch, 2015), and role of intraspecific trait variability in species co‐existence (Crawford et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations